Simulation Modeling of Multi-Junction Solar Cell for Efficiency Improvement - Ali, M. A.; Akram, S. (The Nucleus, 2020)
Current trends in the design of Multi-Junction Solar Cells (MJSC) and quantum dot applications form the backbone of the Concentrated Solar Photovoltaic (CSPs) Systems. There are a number of developments in solar power technology because of their improved power production, high efficiency, high absorption coefficients and cost-effectiveness. Selection of solar photovoltaic (PV) materials of different band gap energies to absorb complete solar spectrum is close to a reality with decrease in price to performance ratio. This paper presents a generalized MJSC simulation model. The present model assumes a mathematical approach, investigating solar cell characteristic curves including current density (Jsc) and power (P) curves concerning the applied voltage for a different number of junctions and by varying the material properties of the multi-junction (MJ). The proposed model simulates different parameters and performance characteristics of two different natures of MJSC including InGaN/AlGaAs/InGaAs Triple Junction Solar Cell (TJSC) and InGaN/InGaN/AlInP/AlInP/AlGaAs/ AlGaAs/AlGaAs Seven-Junction Solar Cell. Simulation results presented in this paper are in agreement with experimental results. Solar cell parameters including short circuit current (Jsc), open circuit voltage (Voc), leakage current (Jo), output power (Pout) have also been calculated in this work. The efficiency (%ðœ‚) of a TJSC for visible light, ultraviolet (UV), visible and infrared (IR) light is presented. The efficiency (%ðœ‚) of seven junction solar cell is calculated to be 63%. Characteristic curves of the solar cell are plotted as a function of voltage for different concentration levels and the number of junctions, which helps to design a solar power array that can operate to its peak power point. The objective of this research is to improve the overall efficiency of MJSC.